1988
DOI: 10.1128/mcb.8.7.2787
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and growth factor pathways of c-fos transcriptional activation require distinct upstream regulatory sequences.

Abstract: Transcription of the c-fos proto-oncogene is rapidly induced in the rat pheochromocytoma PC12 cell line by a wide variety of stimuli, including polypeptide growth factors, phorbol esters, and calcium ion fluxes. We have mapped the upstream sequence requirements for this activation in PC12 cells by analysis of promoter deletion mutants in a transient expression assay. Two distinct pathways of c-fos induction are defined that differ in their requirement for cis-acting DNA sequences. Calcium activation of c-fos t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
216
3
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(232 citation statements)
references
References 44 publications
12
216
3
1
Order By: Relevance
“…À54 to À47), similar to the (TGACGTTT) of the c-fos gene promoter. 26 DNase I protection assays have revealed a footprint in the region extending approximately from nt À52 to À35. 27 The À53 substitution may affect the binding of Oct-1 to the octamer site or some of other transcription factors to the putative Ca 2 þ -responsive element.…”
Section: Discussionmentioning
confidence: 99%
“…À54 to À47), similar to the (TGACGTTT) of the c-fos gene promoter. 26 DNase I protection assays have revealed a footprint in the region extending approximately from nt À52 to À35. 27 The À53 substitution may affect the binding of Oct-1 to the octamer site or some of other transcription factors to the putative Ca 2 þ -responsive element.…”
Section: Discussionmentioning
confidence: 99%
“…Ca2+ mediates gene induction in response to membrane depolarization of various neuronal cell lines and this inducibility has been mapped to CRE-like elements in different promoters (Sheng et al, 1988;Nguyen et al, 1990). In addition, rapid phosphorylation of CREB at has been demonstrated in response to membrane stimulation (Sheng et al, 1991) (Sheng et al, 1991;Dash et al, 1991).…”
Section: Crebmentioning
confidence: 99%
“…Subsequently, it was found that SRF and/or SRF binding sites (CC(A/ T) 6 GG), termed CArG boxes, regulate expression of a wide variety of serum responsive genes (Changelian et al, 1989;Chavrier et al, 1989;Christy and Nathans, 1989;Latinkic et al, 1991;Latinkic and Lau, 1994;Treisman, 1990;Tsai-Morris et al, 1988). SRF also regulates transcription mediated by treatment of cells with neurotrophins (Sheng et al, 1988;Visvader et al, 1988), neurotransmitters and agents that raise intracellular calcium levels (Bading et al, 1993;McDonough et al, 1997;Misra et al, 1994), stress agents, and viral activators (Avantaggiati et al, 1993;Fujii et al, 1992Fujii et al, , 1994. A variety of experiments indicate that SRF is a key transcription factor controlling genes that are involved in cell cycle progression, di erentiation, and development (Arsenian et al, 1998;Croissant et al, 1996;Gauthier-Rouviere et al, 1991;Vandromme et al, 1992).…”
Section: Introductionmentioning
confidence: 99%